2020
DOI: 10.1039/c9ce01391a
|View full text |Cite
|
Sign up to set email alerts
|

Switching-on superparamagnetism in diluted magnetic Fe(iii) doped CdSe quantum dots

Abstract: Chemically prepared, 0.5% Fe(iii)-doped CdSe QDs exhibit superparamagnetism with weak ferromagnetic exchange interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“… 33 Additionally, the electron paramagnetic resonance (EPR) signal intensity of 20 mg-Fe@C/C 3 N 4 -1100 also increased in comparison to that of 20 mg-Fe@C/C 3 N 4 -900, implying that the Fe magnetic states had increased ( Figure 3 b). 34 To sum up, the 20 mg-Fe@C/C 3 N 4 -1100 precatalyst displayed a transformation of Fe microstructure and exhibited excellent magnetism. 29 …”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“… 33 Additionally, the electron paramagnetic resonance (EPR) signal intensity of 20 mg-Fe@C/C 3 N 4 -1100 also increased in comparison to that of 20 mg-Fe@C/C 3 N 4 -900, implying that the Fe magnetic states had increased ( Figure 3 b). 34 To sum up, the 20 mg-Fe@C/C 3 N 4 -1100 precatalyst displayed a transformation of Fe microstructure and exhibited excellent magnetism. 29 …”
Section: Resultsmentioning
confidence: 88%
“…33 Additionally, the electron paramagnetic resonance (EPR) signal intensity of 20 mg-Fe@C/ C 3 N 4 -1100 also increased in comparison to that of 20 mg-Fe@ C/C 3 N 4 -900, implying that the Fe magnetic states had increased (Figure 3b). 34 To sum up, the 20 mg-Fe@C/ C 3 N 4 -1100 precatalyst displayed a transformation of Fe microstructure and exhibited excellent magnetism. 29 To evaluate the CO 2 reduction reaction activity of 20 mg-Fe@C/C 3 N 4 -1100, linear sweep voltammetry (LSV) measurements of a well-prepared catalyst/carbon paper was conducted with N 2 -or CO 2 -saturated 0.1 M KHCO 3 electrolytes from Thus, it can be seen expressly that the prepared electrode was active for CO 2 reduction.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…It reveals that the rGO nanosheet has a non-magnetic response, as expected. On the other hand, Co NPs depict superparamagnetic behavior (minimal coercivity, H C 115 Oe) [22,23]. This behavior observed due to the smaller size of Co NPs (below 20 nm) [24].…”
Section: Resultsmentioning
confidence: 99%
“…The experimental results indicated that 0.02 g of ammonium ferric citrate yielded CDs with the best catalytic effect. Compared with reported procedures for the preparation of CD Fe ( Supplementary Table S1 ) ( Faraji et al, 2018 ; Yue et al, 2019 ; Zhang et al, 2019 ; Yadav et al, 2020 ), our procedure is simpler and requires a shorter hydrothermal reaction time. In addition, only one reagent, ammonium ferric citrate, was used to prepare CD FeN .…”
Section: Methodsmentioning
confidence: 99%